Передмова редактора - Сергій Засєкін (Східноєвропейський журнал психолінгвістики, 2016)
Tbilisi State University in Georgia hosted a truly significant event in June, 2016. Many  scholars and school instructors from six continents gathered there to participate in the 11th Congress of the International Society of Applied Psycholinguistics (ISAPL). The event called Applied Psycholinguistics and Ecology of Language, Culture and Society showed a real potential of psycholinguistics to build intercultural bridges by fostering international contacts and cooperation among researchers, teaching staff who work in the field, and entrepreneurs and governmental officers who are interested in the scientific outcomes of the ISAPL Congress.  This first 2016 volume that includes fourteen contributions by the authors from Bangladesh, Botswana, China, India, Iran, Norway, Sweden, Ukraine, USA embraces the cutting-edge topics of the ISAPL Congress. The most popular topic in the current journal issue is psycholinguistics of first and second or foreign language acquisition. Native tongue, EFL, ESL themes are discussed by Svitlana Buchatska, Olena Zarichna from the Mykhailo Kotsiubynskyi State Pedagogical University of Vinnytsia (Ukraine); Melisa Grabovac from the Stockholm University (Sweden) and Oleksandr Kapranov from the University of Bergen (Norway); Taichi Yamashita and Hsiao Hsuang Hung from the Texas Tech University (USA); V. Kavitha and Padmasani Kannan from the Dr.M.G.R. Educational and Research Institute University (India); Shafinaz Sikder from the BRAC University (Bangladesh); Javad Ahmadi Fatalaki from the Allameh Tabataba'i University (Iran) together with Runhan Zhang from the Central University of Finance and Economics (China). An important part of the education philosophy in the field of psycholinguistics is introducing readers to genuine translation studies research, undertaken by two Ukrainian scholars, Tetiana Andriyenko from the Taras Shevchenko National University of Kyiv and Taras Shmiher from the Ivan Franko National University of Lviv, who offer cognitive solutions to translation problems. A psycholinguistic and discourse analysis toolkit of verbal and pictorial units in media and communication is applied by Oleksandr Kholod from the Kyiv National University of Culture and Art (Ukraine); Valentyna Ushchyna and Larysa Makaruk from the Lesya Ukrainka Eastern European National University (Ukraine). Zoriana Matsyuk and Maria Fenko from the same institution suggest an original approach of fairy tale therapy for the speech development in pre-school children. Olusegun Emmanuel Afolabi from the University of Botswana gives an overview of clinical psycholinguistics approaches to attention deficit hyperactivity disorder (ADHD) in children.   For better visibility and collaboration, the articles are published in open access on the journal site: http://eejpl.eenu.edu.ua/index.php/eejpl/home, and deposited both in the scientific electronic archives of the European Union: https://zenodo.org and in the EENU Publishers repository: http://esnuir.eenu.edu.ua. We are very thankful both to the authors and the reviewers who invested their time and efforts in the volume production, evaluation and knowledge sharing process. We strongly believe that the research outcomes and goals achieved by the international team of the authors will be a valuable contribution to better understanding the ecology of human linguistic and cultural relations in today’s rapidly changing society.References11th Congress of the ISAPL 2016: Applied Psycholinguistics and Ecology of Language, Culture and Society. Tbilisi State University. Retrieved from: http://isapl.tsu.ge. Serhii Zasiekin,ISAPL member